Correlated Sensory and Sympathetic Innervation Between the Acupoint BL23 and Kidney in the Rat - Zhang, Zhiyun; Xu, Dongsheng; Wang, Jia; Cui, Jingjing; Wu, Shuang; Zou, Ling; Shen, Yi; Jing, Xianghong; Bai, Wanzhu (Frontiers in Integrative Neuroscience, 2021)
Objective: To investigate the sensory and sympathetic innervations associated with both acupoint “Shenshu” (BL23) and kidney in the rat for insight into the neuronal correlation between the Back-Shu Point and its corresponding visceral organ. Methods: The BL23 and kidney were selected as the representative acupoint and visceral organ in this study, in which their local nerve fibers were examined by using double fluorescent immunohistochemistry with calcitonin gene-related peptide (CGRP) and tyrosine hydroxylase (TH). Meanwhile, their neuronal correlation in the dorsal root ganglia (DRGs), spinal cord, and sympathetic (paravertebral) chain were investigated using a double fluorescent neural tracing technique with Alexa Fluor 488 and 594 conjugates with cholera toxin subunit B (AF488/594-CTB). Results: The local tissue of acupoint BL23 and the fibrous capsule of kidney distributed abundantly with CGRP- and TH-positive nerve fibers, corresponding to their sensory and sympathetic innervation. On the other hand, the sensory neurons associated with acupoint BL23 and kidney were labeled with AF488/594-CTB and distributed from thoracic (T) 11 to lumbar (L) 3 DRGs and from T10 to L2 DRGs, respectively, in which some of them in T12-T13 DRGs were simultaneously labeled with both AF488/594-CTB. Also, postganglionic neurons associated with both acupoint BL23 and kidney were found in the sympathetic chain at the same spinal segments but separately labeled with AF488-CTB and AF594-CTB. Conclusion: Our study demonstrates the neural characteristics of the acupoint BL23 and kidney in the rat from the perspective of neurochemistry and neural pathways, providing an example for understanding the neuronal correlation between the Back-Shu Points and their corresponding visceral organs. These results suggest that the stimulation of the Back-Shu Points may regulate the activities of the target-organs via the periphery sensory and sympathetic pathways.